Rethinking the Cyber Regulatory Framework for Data Access Consent: Legal Challenges and Reform in the Hashemite Kingdom of Jordan - Mohammed Ali Khaled Al-Shurman; Wail Abouabaid; Hasan Jassam Ahmed; Maher Ali Ahmad Al-Khaldi; Jamal Awwad Alkharman; Hamdan Ghunemat (Nusantara: Journal of Law Studies, 2026)
The rapid expansion of digital technologies and cross-border data flows has fundamentally transformed the ways in which personal data are accessed, processed, and exchanged, creating new challenges for cyber regulation and individual data rights. In the Hashemite Kingdom of Jordan, the development of data protection regulations has not yet fully addressed the legal complexities associated with data access consent, technological transformation, and emerging forms of digital exploitation. This study aims to critically examine Jordan’s cyber regulatory framework governing personal data access and consent by evaluating its conceptual foundations, legislative coherence, enforcement capacity, and responsiveness to contemporary technological developments. The study employs a descriptive-analytical legal approach to examine statutory provisions, regulatory instruments, and relevant legal principles governing personal data, consent, privacy, intellectual property, and cybersecurity. A comparative approach is also employed selectively to identify regulatory practices from contemporary data protection frameworks that may inform legal reform in Jordan. The findings demonstrate a persistent regulatory gap between the pace of technological innovation and the capacity of existing legal mechanisms to provide effective and enforceable protection. Particular weaknesses emerge in the regulation of informed consent, personal data rights, data-related intellectual property interests, institutional enforcement, and cross-border data transfers. The study further finds that consent-based regulation can serve as a central mechanism for reconciling individual autonomy, data protection, and legitimate access to personal data, provided that consent is transparent, informed, specific, and effectively enforceable. Scientifically, this study contributes a reform-oriented framework for strengthening Jordan’s cyber regulatory architecture through legislative modernization, clearer institutional responsibilities, stronger cross-border cooperation, accountable data-consent platforms, technological safeguards, and enhanced public legal awareness. These reforms are essential for developing a rights-based and technologically responsive data governance regime in Jordan.